Effects of Morning Versus Evening Home-Based Exercise on Subjective and Objective Sleep Parameters in Older Adults: A Randomized Controlled Trial. (May 2021) - Seol, Jaehoon; Fujii, Yuya; Inoue, Taiki; Kitano, Naruki; Tsunoda, Kenji; Okura, Tomohiro
Objective: This study aimed to determine whether the timing of exercise influenced the effects of home-based low-intensity stepping exercises on the sleep parameters of older adults. Method: For 8 weeks, 60 healthy older adults participated in a randomized controlled trial, performing low-intensity aerobic exercise (70-80 bpm) for about 30 minutes every day at home, either in the morning (from waking until 12:00) or evening (18:00 to bedtime). Results: In the evening exercise group, both subjectively and objectively measured sleep latency significantly improved throughout the intervention. Further, postintervention subjective sleep satisfaction was significantly higher in the evening group (6.2 ± 1.3 points) than in the morning group (5.2 ± 1.4 points; P = .006). Additionally, sleep variables related to evening exercise had larger effect sizes (Cohen d ) than those performed in the morning. Conclusion: Engaging in low-intensity stepping exercises during the evening is potentially a useful nonpharmacological approach to improving sleep quality among older adults.